Adaptation, summer survival and autumn dormancy of lucerne cultivars in a south European Mediterranean region (Sardinia) - Pecetti L.; Carroni A.M.; Annicchiarico P.; Manunza P.; Longu A.; Congiu G. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Some 16 lucerne cultivars of various geographic origins (Europe, north Africa, USA, Australia), including recent varieties as well as traditional cultivars, were evaluated in a rainfed environment of southern Sardinia (long-term annual rainfall: 382 mm) with the following objectives: (i) to compare adaptation and summer survival of different germplasm types and dormancy classes (ranging from moderate to non-dormant); and (ii) to define a genetic base for future breeding of drought-tolerant varieties targeted to south European Mediterranean environments. Results are provided for two-year dry matter yield, stand density after the second summer, autumn dormancy rating and phenology. These preliminary results suggest that drought-tolerant material may preferably be located in south European landraces which evolved under rainfed, drought-stressed environments, or in US or Australian varieties which were selected in stress conditions. North-African landraces, mostly evolved under irrigated conditions, tended to be less adapted to drought-stress conditions.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)